Dense breast – a breast cancer risk factor - Połać, Ireneusz; Wilamowska, Agnieszka; Stetkiewicz, Tomasz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Breast cancer is the most common neoplastic disease in women. Prevalence of this cancer increases with age, reaching its peak during the postmenopausal period. Worldwide researchers try to create asssessment models to evaluate breast cancer risk and preventive methods. One of these methods should be mammographic breast density. In this paper we review the most common mammographic assessment techniques. Also we present a hypothesis concerning dense breast and risk factors contributing to this phenomenon.